Proyecto de factibilidad para la creación de una hostería agro turística en Machachi - González Zumárraga, María Isabel (2004)
The present work of qualifications constitutes a project of feasibility for the creation of an Inn tourist Agro in the zone of Aloasi-Machachi, the same one that was called a “PARAMO GRANDE”. This work is divided in four parts distributed in seven chapters: In the first part(report) there are exposed the results of the investigation(research) of market realized to know the potential clients and the competition(competence), which will use as guide for the capture of decisions